Methodology for assessing the level of biological risk of emergence and spread of infectious and parasitic diseases of potato by parameters of mechanisms and pathways of pathogen transmission - Dorokhov, Alexey; Sibirev, Alexey; Lyashchuk, Yulia; Teterin, Vladimir; Panferov, Nikolay (Frontiers in Sustainable Food Systems, 2025)
This research presents quantitative assessment of the biological risk level associated with spread of infectious and parasitic potato plant (Solanum tuberosum) diseases, based on the parameters of transmission and contagion mechanisms and pathways. The authors conducted a point-rating analysis of threats of potato infection or infestation with pathogens of different etiologies: bacterial, viral, helminthic and mycotic. The developed system of analysis is flexible and implies regular monitoring and data update in case of the globalization and world trade bring new strains of infections and varieties of parasites, which will be able to adapt to the climatic conditions of a particular region and the means of chemical plant protection. As a result, the combination of modern approaches to the field of potato plant disease detection and the proposed methodology will allow the development of a comprehensive system for monitoring and forecasting the spread of infections, which will make it possible to take timely and effective measures to protect the crop. The use of optical methods in combination with the analysis of data on pathogens will increase the accuracy of diagnostics and the effectiveness of prevention, contributing to the sustainable development of agriculture.